Theories of federal-state relationship - Rasyikah Md Khalid,; Faridah Jalil, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Federalism refers to an arrangement between several States which agree to be united together as a nation state. The administration of a federal state will be shared between a central government and the member States. There are two major types of federalism; dual federalism and cooperative federalism. While the former holds that the federal and state governments are co-equals with specific powers granted by the constitution, the latter denotes that although federal government is supreme over States, both acts cooperatively to solve common problem. To appreciate the meaning of federalism and federal-state relation, different approaches towards federalism will be analyze. It demonstrates how different concepts of federal-state relation can improve the management of a country and solve conflict between different levels of governments.